Users' perception of the reader services and faciliities of the Bulacan Provincial Library - Perez, Arlene M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
The study is to identify and improve the strong and weak aspects of the provincial library's reader services and facilities and to address the provincial government to upgrade the quality of the library.
This study seeks to determine the following objectives: 1. To determine the users' perception on the library facilities relative to : Book and non-book materials, library furniture, light and ventilation, seating capacity, space for the collection; 2. To know the users' perception on the services relative to: Guidance in the users' selection of books, guidance in the use of library facilities; assistance in research done at the library; informing about new library acquisitions, upgrading collection; 3. To list comments and recommendations to improve the library's services and facilities.
The descriptive method of research is applied, using a two part questionnaire as the primary instrument in data gathering with supplementary interviews. Two different sets of questionnaires are prepared, one for the clientele and the library staff. It consist of personal information, opinion about the library's services and facilities. The survey is conducted with a time frame of one week. The samples are randomly chosen-each are given a survey questionnaire as they enter the premises of the library.
Computer print out.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Bulacan Provincial Library; Library use studies -- Philippines -- Bulacan; Public libraries -- Philippines -- Bulacan